Multiwavelength observations of a new black-widow millisecond pulsar PSR J1544−2555 - Belmonte Díaz, S.; Thongmeearkom, T.; Phosrisom, A.; Breton, R. P.; Burgay, M.; Clark, C. J.; Nieder, L.; Mayer, M. G.F.; Becker, W.; Barr, E. D.; Buchner, S.; Das, K. K.; et al. (Monthly Notices of the Royal Astronomical Society, 2025)
We report the discovery of a new black-widow millisecond pulsar, PSR J1544−2555, associated with the Fermi-Large Area Telescope (LAT) source 4FGL J1544.2−2554. Optical, radio, and gamma-ray observations confirmed its nature as a compact spider binary system. Optical photometry from ULTRACAM revealed a ∼2.7-h orbital period, guiding MeerKAT observations that detected ∼2.4-ms radio pulsations. Subsequent timing campaigns using the Murriyang Parkes Telescope, the Effelsberg 100-m Radio Telescope, and the Nanc¸ay Radio Telescope allowed us to obtain a preliminary timing solution, which enabled us to find gamma-ray pulsations. The final timing solution, spanning 16 yr of Fermi-LAT gamma-ray data, also displays orbital period variations typical of spider pulsars. X-ray observations from eROSITA indicate non-thermal emission, but the relatively low count rate prohibits the search for X-ray pulsations. Optical light curve modelling using Icarus suggests the asymmetry is best explained by a spot model, where uneven heating creates localized temperature variations on the companion. While the optical spectra we obtained are compatible with the physical properties we infer for the companion star, they were not of sufficient signal-to-noise to allow for radial velocity measurements, thus limiting constraints on the neutron star’s mass. The observed bluer colour near the light curve minimum suggests possible non-thermal emission from intrabinary shocks, supported by the presence of an X-ray source. This discovery exemplifies the proven capability of the Fermi-LAT catalogue in identifying millisecond pulsar candidates and highlights the role of optical surveys in detecting variable sources suitable for radio follow-up.
CRIS-Team Scopus Importer:2025-10-24
Keywords: binaries: general; gamma-rays: stars; pulsars: general; pulsars: individual: PSR J1544−2555